Addition of Moringa Leaf Extract and Natural Sweeteners of Palm Sugar to The Characteristics of Moringa Pudding - Ni Luh Putu Dian Windari; Luh Suriati; I Nyoman Rudianta (SEAS (Sustainable Environment Agricultural Science), 2021)
Pudding is a type of dessert. It tastes sweet and has a soft texture. Efforts are made on making pudding that can be functional by adding Moringa leaf extract and palm sugar. The purpose of this study was to determine the characteristics of water content, reduced sugar content, pH, texture and antioxidant activity as well as subjective assessments including aroma, color, texture and overall acceptance of Moringa pudding added with natural sweeteners of palm sugar. The research was conducted in September 2019-February 2020 at the Food Analysis Laboratory of the Faculty of Agriculture, Warmadewa University and Udayana University. Using a factorial experiment with a Completely Randomized Design (CRD) consisting of 2 factors: Factor I, Moringa leaf extract concentration (2.5%, 5.0%, 7.5% and 10.0%). Factor II, the addition of palm sugar (5.0%, 7.5% and 10.0%). The objective analysis of pudding produced from the treatment of Moringa leaf extract 10.0% palm sugar 10.0% while the subjective assessment of pudding produced from the treatment of Moringa leaf extract 5.0% palm sugar 10.0% (like-very like) with the characteristics of pudding Moringa is the water content of the addition of Moringa leaf extract 74,138% Palm sugar 63,172%, Reducing sugar content adding Moringa leaf extract 15,239% Palm sugar 15,515%, pH adding Moringa leaf extract 6,733 Palm sugar does not affect, the texture of adding Moringa leaf extract and Palm sugar 5,612 N Antioxidant activity of addition of Moringa leaf extract 22,275 mg / L GAEAC palm sugar 21,676 mg / L GAEAC.